Modelos de financiación y generación de ingresos: una guía útil - Serra, Eugí¨nia (Anuario ThinkEPI, 2015)
Reseña del informe:Maron, Nancy (2014). A guide to the best revenue models and funding sources for your digital resources. JISC-Strategic Content Alliance, IthakaÂ S+R.http://sr.ithaka.org/sites/default/files/reports/Jisc_Report_032614.pdf